Crystal Structure and Electrochemical Property of Tetrazole Complex of Copper [Cu(pta)2(NO3)2(H2O)2] (pta = 1-Phenyl-1H-tetrazole) - Liu, E.; Jian, Fangfang (Asian Journal of Chemistry, 2019)
A new compound, [Cu(pta)2(NO3)2(H2O)2] (pta = 1-phenyl-1H-tetrazole) has been synthesized and characterized by IR, elemental analysis and single-crystal X-ray diffractions. X-ray structural analysis reveals that each Cu atom is coordinated by two pta molecules, two nitrate ions and two water molecules to form octahedral coordination geometry. O(1w) atoms of the water molecules serve as H-donor to interact with the nitrate oxygen atoms O(2), O(3) (H-acceptor) and form 1D hydrogen-bond ladder chains. These chains then, construct a 2D network layer via π-π stacking interactions between the five-membered ring of tetrazole and the six-membered ring of benzene. The 3D framework was constructed through the hydrogen bonds of C(7)-H(7A)····O(3). The behaviour of cyclic voltammetry of the compound on three-electrode cell showed an irreversible process.